The Circulating Role: Who is the most Appropriate Care Provider? - Bauce, Cathy; Braid, Marjorie; Gould, Judy; Hopwood-Jones, Laurel; Moroz, Mary; Radcliffe, Kathy; Ross, Joanne; Tyndall, Judi; Young, Alaine (Operating Room Nurses Association of Canada Journal, 1998)
This article describes the long and arduous journey to the development of the" Nursing Position Statement - Appropriate Care Provider for the Operating Room in Hamilton and Burlington, Ontario. From the first meeting to the final presentation of the Position Statement to management, it took over a year of intense review. The entire process was done in consultation with the College of Nurses of Ontario, Operating Room Management, educators and staff nurses.